2012
DOI: 10.1007/s13197-012-0901-y
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of spray drying process for developing seabuckthorn fruit juice powder using response surface methodology

Abstract: The response surface methodology was used to optimize the spray drying process for development of seabuckthorn fruit juice powder. The independent variables were different levels of inlet air temperature and maltodextrin concentration. The responses were moisture, solubility, dispersibility, vitamin C and overall color difference value. Statistical analysis revealed that independent variables significantly affected all the responses. The Inlet air temperature showed maximum influence on moisture and vitamin C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 10 publications
2
13
0
2
Order By: Relevance
“…The moisture-differentiating factors could be temperature during freeze drying (too low cause sublimation barrier) [ 13 ], inlet and outlet temperatures during spray drying and percentage of carrier agents [ 19 ]. Selvamuthukumaran and Khanum [ 20 ] found that the inlet air temperature, followed by maltodextrin concentration, had the maximum effect on the moisture content of the spray-dried sea buckthorn juice. In the same research, they also found that the optimal values of these parameters were, respectively, 162.5 °C and 1:4 for maltodextrin:fruit slurry.…”
Section: Resultsmentioning
confidence: 99%
“…The moisture-differentiating factors could be temperature during freeze drying (too low cause sublimation barrier) [ 13 ], inlet and outlet temperatures during spray drying and percentage of carrier agents [ 19 ]. Selvamuthukumaran and Khanum [ 20 ] found that the inlet air temperature, followed by maltodextrin concentration, had the maximum effect on the moisture content of the spray-dried sea buckthorn juice. In the same research, they also found that the optimal values of these parameters were, respectively, 162.5 °C and 1:4 for maltodextrin:fruit slurry.…”
Section: Resultsmentioning
confidence: 99%
“…The development of SFJP (Fig. ) was carried out as per the procedure of Selvamuthukumaran and Khanum ().…”
Section: Methodsmentioning
confidence: 99%
“…The addition of maltodextrin to the feed solution prior to spray drying increased the total solids content and reduced the total amount of water available for evaporation. Previous studies showed that increasing the inlet air temperature increased the drying rate, and, hence, the moisture content of the powder produced [17,18].…”
Section: Powder Yieldmentioning
confidence: 96%